Evaluasi Pelaksanaan Pencegahan dan Pemberantasan Perdagangan Perempuan di Perbatasan Kabupaten Sambas Kalimantan Barat - Rianawati Rianawati; Wagiyem Wagiyem (Research and Development Agency Ministry of Home Affairs, 2019)
Women's trafficking is the most classic gender issue in the course of human history. This issue often appears and as if there is virtually no solution, although various prevention and eradication efforts have been made by various parties. However, based on observations and interviews, various programs have not been explored even though many budgets have been issued. This research approach is qualitative with a descriptive method in order to describe the phenomenon occurring in the field according to the actual fact. As the source of data is the government of Sambas district, the empowerment and protection of women and children (P2TP2A, the Department of Cross-sector, non-governmental organizations, and the community. Data collection techniques are in-depth interviews and documentation. This research finding is: 1. The Government who participated directly and committed to TPPO (women) is the Bappeda, DP3AP2KB, Department of Labor, and immigration. B. group participation but not committed in TPPO (women) namely, the Education Office; C Group participation and commitment in eradication but not involved in the prevention of the trafficking of women namely the social service and the Court; D. The party involved but not committed in the TPPO of the Police Women (Polres Sambas); 2. Planning and implementation of prevention and eradication of Women's trafficking in Sambas district is less than optimal. 3. Monitoring and evaluation of the prevention and eradication of Women's trade in Sambas district is less than optimal. 4. Available facilities and infrastructure related to the prevention and eradication of the trafficking of women is still insufficient and far from expectation 5. Lack of public understanding of TPPO (female).